Mst2 Controls Bone Homeostasis by Regulating Osteoclast and Osteoblast Differentiation. (31st May 2015) - Lee, Jongwon; Youn, Bang Ung; Kim, Kabsun; Kim, Jung Ha; Lee, Da‐Hye; Seong, Semun; Kim, Inyoung; Han, Seung‐Hee; Che, Xiangguo; Choi, Je‐Yong; Park, Yong‐Wook; Kook, Hyun; et al.
ABSTRACT: Mammalian sterile 20‐like kinase 2 (Mst2) plays a central role in the Hippo pathway, controlling cell proliferation, differentiation, and apoptosis during development. However, the roles of Mst2 in osteoclast and osteoblast development are largely unknown. Here, we demonstrate that mice deficient in Mst2 exhibit osteoporotic phenotypes with increased numbers of osteoclasts and decreased numbers of osteoblasts as shown by micro–computed tomography (µCT) and histomorphometric analyses. Osteoclast precursors lacking Mst2 exhibit increased osteoclastogenesis and Nfatc1, Acp5, and Oscar expression in response to receptor activator of NF‐κB ligand (RANKL) exposure. Conversely, Mst2 overexpression in osteoclast precursors leads to the inhibition of RANKL‐induced osteoclast differentiation. Osteoblast precursors deficient in Mst2 exhibit attenuated osteoblast differentiation and function by downregulating the expression of Runx2, Alpl, Ibsp, and Bglap . Conversely, ectopic expression of Mst2 in osteoblast precursors increases osteoblastogenesis. Finally, we demonstrate that the NF‐κB pathway is activated by Mst2 deficiency during osteoclast and osteoblast development. Our findings suggest that Mst2 is involved in bone homeostasis, functioning as a reciprocal regulator of osteoclast and osteoblast differentiation through the NF‐κB pathway. © 2015 American Society for Bone and Mineral Research.